2005
DOI: 10.1891/088667005780927467
|View full text |Cite
|
Sign up to set email alerts
|

“Ordinary People” and “Death Work”: Palestinian Suicide Bombers as Victimizers and Victims

Abstract: Applying criminological/victimological concepts and theories, the study addresses the social processes involved in Palestinians' suicide terrorism and describes Palestinians' pathways to suicide bombing. The data are derived from in-depth interviews of 7 male and female Palestinians serving prison sentences in Israel for attempted suicide bombing. The social background, context, and experiences of the interviewees, including their recruitment, interactions with the organizations that produce suicide bombing, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In a content analysis of the statements suicide bombers give before their death, a strong sense of victimization was identified as one of the core motives, combined with a perceived lack of effective alternatives to violence (Hafez, 2006). Likewise, in-depth interviews with imprisoned suicide bombers whose attempted attack had failed showed that “the participants’ social identity as Palestinians, who are dispossessed, oppressed, and humiliated, was a recurrent theme in discussing their lives” (Berko & Erez, 2005, p. 609). These interviews also revealed the deep impact of parents’ narratives about 1948 or 1967, as well as the humiliation through Israeli soldiers experienced at checkpoints.…”
Section: Victim Beliefs In the Israeli–palestinian Conflictmentioning
confidence: 99%
“…In a content analysis of the statements suicide bombers give before their death, a strong sense of victimization was identified as one of the core motives, combined with a perceived lack of effective alternatives to violence (Hafez, 2006). Likewise, in-depth interviews with imprisoned suicide bombers whose attempted attack had failed showed that “the participants’ social identity as Palestinians, who are dispossessed, oppressed, and humiliated, was a recurrent theme in discussing their lives” (Berko & Erez, 2005, p. 609). These interviews also revealed the deep impact of parents’ narratives about 1948 or 1967, as well as the humiliation through Israeli soldiers experienced at checkpoints.…”
Section: Victim Beliefs In the Israeli–palestinian Conflictmentioning
confidence: 99%
“…On the Palestinian side, Berko and Erez (2005) noted that Palestinians’ collective identity is not only shaped by their families, peer groups, and religious and national groups, but also by their internalized collective memory of injustice, defeat, and dishonor that was done to their people in the nakba (“the catastrophe”) and later. One reason for these different collective memories is due to the different life experiences that Israelis and Palestinians have had: as victims of war, the Holocaust, terrorism, and the rebirth of a state in the Israeli case; and as victims of dispossession of land, military violence, occupation, and as refugees without a state of their own in the Palestinian case.…”
Section: Collective Memory Trauma and Victimhood In The Case Of Jewis...mentioning
confidence: 99%
“…In all classes it is seen that family support for non-violence is a (more or less) present protective factor. Previous research has shown that family members, especially mothers, have the power to dissuade their loves ones from carrying out a suicide terrorism act (Berko & Erez, 2005). Involvement of the family may thus prove to be an important intervention in the context of disengagement for all classes.…”
Section: Discussionmentioning
confidence: 99%
“…Research into suicide bombers indicated that family members, especially mothers, can detect behavioral precursors to suicide in their offspring (e.g., changes in routines). Therefore, Berko and Erez (2005) stated that mothers can detect suicide plans and do have the power to dissuade their loved ones from carrying them out.…”
Section: Introductionmentioning
confidence: 99%